Perancangan dan Analisa Frame Sepeda Pengangkut Gabah - Mariudin, Rachmad; Gunawan, Yuspian; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2018)
This study aims to determine the stress distribution on grain carriers. In this study frame construction was designed using autodesk inventor software and simulation using ansys software. Carbon stell material with a load of 175 kg is used as a frame material in this analysis. The results show that the maximum stress that occurs in the frame reaches 38,238 N/m2 from the simulation results while in manual calculations the voltage is reached 33,981 N/m.Keywords: Frames, Ansys software simulation, voltage distribution.